2017
DOI: 10.1097/ee9.0000000000000005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of night-time temperatures on cause and age-specific mortality in London

Abstract: This leaves scope for more detailed assessments of the thermal characteristics of the night and their impact on health. 18 Heat-related mortality is higher in urban areas than in rural and surrounding areas 9,13,19,20 because of the urban heat islands effect. 9 The temperature difference between urban and rural areas shows a distinct hourly variation, where the greatest differences are observed in the evenings and early morning hours. 21,22 Cardiac and cerebrovascular events also exhibit a similar diurnal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 48 publications
2
101
0
2
Order By: Relevance
“…The nighttime bluespace warming and humidification exacerbate the existing urban thermal discomfort at the dense urban core close to the shore by 4.2°C in the hottest month with annual average warming by 3.5±1.2°C. This magnitude can be influential as strong evidence has been established between hot nighttime temperatures and mortality (Murage et al 2017). We show for the first time that, remarkably, the degree of bluespace warming depends upon the amount of vegetation at the city scale.…”
Section: Discussionmentioning
confidence: 60%
“…The nighttime bluespace warming and humidification exacerbate the existing urban thermal discomfort at the dense urban core close to the shore by 4.2°C in the hottest month with annual average warming by 3.5±1.2°C. This magnitude can be influential as strong evidence has been established between hot nighttime temperatures and mortality (Murage et al 2017). We show for the first time that, remarkably, the degree of bluespace warming depends upon the amount of vegetation at the city scale.…”
Section: Discussionmentioning
confidence: 60%
“…Apart from the more commonly analyzed daytime influence of high temperatures, nighttime extremes have also been referred as causing an additional burden to health (Murage et al 2017) and the environment (Miralles et al 2014, Gouveia et al 2016. Here, and despite the stronger relationship found between drought condictions and daytime extreme events, the nightime influence is not negligible.…”
Section: Discussionmentioning
confidence: 91%
“…The data from this site has already been used in previous studies, and was shown to be suitable to represent city-wide air temperature conditions [7,46]. We used T mean , as it was shown to be more suitable than, or at least as good as, the daily maximum or minimum air temperature in order to describe heat-related mortality in cities [8,46,[48][49][50][51]. No significant temporal long-term trend in T mean could be observed during the study period.…”
Section: Datamentioning
confidence: 99%